Places: Widening the Scope of an Ecological Approach to Perception–Action With an Emphasis on Child Development. Issue 1 (2nd January 2018) - Heft, Harry
ABSTRACT: An animal's habitat is filled with places that support activities in daily life. There are places, for example, that afford sleeping, eating, hiding, and gathering with others. Most places reflect the environment's nested structure. Even as perception–action is coupled to structure at the level of affordances, it is also coupled especially in human societies to dynamic structures at the level of places within which affordances are nested. These places have a distinctive complexity arising from the collective actions of individuals. For this reason, place-specific activities in human habitats are nearly always embedded in collective social practices . If children are to function adaptively as social beings in the community where they develop and live from day to day, they must learn not only where such places are located but also and critically how to participate in them . Owing to shared intersubjective intentions that give rise to places as behavior settings, individuals' actions in community settings are normatively constrained in the course of their participating in those settings. Consideration of the place within which perception–action is nested is indispensable if we hope to attain an adequate understanding of human perception–action in community settings as well as in some of the settings where research is conducted.